POLA DAN FORMULASI PEMBEBASAN KETERGANTUNGAN PEDAGANG KECIL DARI RENTENIR: Studi Kasus di Pasar Ngemplak Tulungagung - Faizun, Mochammad; Nurohman, Dede; Umam, Syamsul (An-Nisbah: Jurnal Ekonomi Syariah, 2020)
This study aims to determine patterns and formulations for relieving community dependency from moneylender practices. The variables used in this study are traders in the Ngemplak Tulungagung market. Data analysis uses descriptive qualitative methods. This study focuses its study on efforts to understand the practices of loan sharks in depth, understand deeply the capital needs of traders who become their customers in business development, and see the existence and role financial institutions around the location of moneylender practices that they have played, as well as the government's perceptions and efforts in tackling these rent practices. The results of this study, first, the main cause of Ngemplak market traders' dependence on moneylenders is the ease that traders can get when borrowing from moneylenders compared to when borrowing from banks and other capital providers. Second, coordination between financial institutions, the government, Baznas and Ngemplak market traders is needed to equalize the vision. Mission, and the goal of liberating traders from dependence on moneylenders Keywords: moneylenders, dependencymoneylender practices